2012
DOI: 10.1128/aac.00585-12
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Toxicity of Proline-Rich Antimicrobial Peptides Shuttled into Mammalian Cells by the Cell-Penetrating Peptide Penetratin

Abstract: The health threat caused by multiresistant bacteria has continuously increased and recently peaked with pathogens resistant to all current drugs. This has triggered intense research efforts to develop novel compounds to overcome the resistance mechanisms. Thus, antimicrobial peptides (AMPs) have been intensively studied, especially the family of proline-rich AMPs (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 37 publications
1
54
0
1
Order By: Relevance
“…With a view toward augmenting innate immunity, HBD-2 mRNA transfection into monocyte-derived macrophages was shown to be effective against Mycobacterium tuberculosis, where the AMP and bacterium inexplicably colocalized in phagosomes (37). Similarly, insect-derived short proline-rich antimicrobial peptides (48) linked to a cell-penetrating peptide, penetratin, entered the cytoplasm of two mammalian cell lines without marked toxicity; intracellular resistance was increased against Micrococcus luteus but not against Escherichia coli (48). The insectderived peptides show homology to mammalian heat shock proteins, but concern about potential cross-reactivity with host proteins and an autoimmune response may limit their clinical utility.…”
Section: Discussionmentioning
confidence: 99%
“…With a view toward augmenting innate immunity, HBD-2 mRNA transfection into monocyte-derived macrophages was shown to be effective against Mycobacterium tuberculosis, where the AMP and bacterium inexplicably colocalized in phagosomes (37). Similarly, insect-derived short proline-rich antimicrobial peptides (48) linked to a cell-penetrating peptide, penetratin, entered the cytoplasm of two mammalian cell lines without marked toxicity; intracellular resistance was increased against Micrococcus luteus but not against Escherichia coli (48). The insectderived peptides show homology to mammalian heat shock proteins, but concern about potential cross-reactivity with host proteins and an autoimmune response may limit their clinical utility.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the relative peak areas should reflect the peptide molar ratios very well. In contrast, the signal corresponding to [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Api88 increased continuously over the observation period, but its peak area was still below 10% after 2 h (Fig. 1A).…”
Section: Resultsmentioning
confidence: 82%
“…S1), which points to the C-terminally truncated peptides [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Api88 and 1-16 Api88, respectively. The peak area of [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Api88 increased very rapidly during the first 30 min to 70% of the initial peak area of Api88 and then showed a further slight increase to 80% within the next 30 min, before decreasing slowly afterwards (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inside the cell, the AMPs (pyrrhocoricin and drosocin) interact with the target, which is mainly the 70 kDa heat shock protein DnaK. They can also interfere with DNA and RNA synthesis by binding to nucleic acids (Kragol et al, 2002;Li et al, 2006;Nicolas, 2009) and have been shown to target E. coli, Klebsiella pneumoniae, Pseudomonas aeruginosa and Acinetobacter baumannii (Mattiuzzo et al, 2007;Hansen et al, 2012).…”
Section: Working Mechanism Of Ampsmentioning
confidence: 99%